2011
DOI: 10.1163/156855412x626234
|View full text |Cite
|
Sign up to set email alerts
|

Interface Stability of Microencapsulated-Paraffin Filled Epoxy Composites: Effect of Methylation on Melamine–Formaldehyde Shell Material

Abstract: Microcapsules containing phase change materials (microPCMs) can be filled in polymeric matrix forming smart temperature-controlling composites. The aim of this study was to investigate the composite interface stability of microPCMs/epoxy composites. Paraffin was applied as the phase change materials. Methanolmelamine-formaldehyde (MMF) and melamine-formaldehyde (MF) were both used to form the shell of microPCM by in-situ polymerization. The investigation focused on studying the effect of methylation and interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The FTIR spectra shown in Figure 3 are similar to those reported for other microencapsulated PCMs [33,37,43]. The intensity of the peak at 1730 cm -1 corresponding to the carbonyl group is much higher for PCM-E as observed in Figure 3(a), which represents a stronger bond between the associated carbonyl groups.…”
Section: (A) (B)supporting
confidence: 77%
See 1 more Smart Citation
“…The FTIR spectra shown in Figure 3 are similar to those reported for other microencapsulated PCMs [33,37,43]. The intensity of the peak at 1730 cm -1 corresponding to the carbonyl group is much higher for PCM-E as observed in Figure 3(a), which represents a stronger bond between the associated carbonyl groups.…”
Section: (A) (B)supporting
confidence: 77%
“…A larger core content is generally likely to result in poor formation of the shell walls and thus decreases the stability of the microcapsules [42]. However, the results in the subsequent sections in this paper suggest that for PCM-E, this problem has been overcome, possibly through chemical modification of MF [40,43]. Fourier Transform Infrared (FTIR) spectra of both the PCMs are shown in Figure 3(a).…”
Section: Characterization Of the Microencapsulated Pcmsmentioning
confidence: 91%
“…No interface debonding emerged between microcapsules and bitumen after a mixture and a temperature change. An interphase region is comprised of polymer molecules that are bound at the filled particles surface, and they exhibit unique physical and chemical properties [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] In order to develop FRP-incorporated multifunctional composites, it is necessary to fully understand the inclusion effect of phase change materials with respect to the structural and thermophysical properties of composite laminates. Although several studies have reported on the inclusion effect of different microcapsules in polymer matrices, [9][10][11][12][13][14] the failure mechanisms associated with the presence of microencapsulated phase change materials (micro-PCMs) in FRP composites have not been broadly addressed in the open literature. This paper reports an experimental study on incorporating micro-PCMs in glass-epoxy composites and characterising their mechanical and thermal properties.…”
Section: Introductionmentioning
confidence: 99%